Fuzzy Logic Approach for Hybrid Position/Force Control On Underwater Manipulator. - Arshad, Mohd Rizal; Mat Suboh, Surina; Abd Rahman, Irfan; Mahyuddin, Mohd Nasiruddin (2007)
A fuzzy logic control method for hybrid position/force control of underwater manipulator is proposed in this paper.